2011
DOI: 10.1183/09031936.00102610
|View full text |Cite
|
Sign up to set email alerts
|

Lack of involvement of type 7 phosphodiesterase in an experimental model of asthma

Abstract: Type 7 phosphodiesterases (PDE7) are responsible for the decrease of intracellular cyclic AMP (cAMP) in many cells involved in allergic asthma by suppressing their potential to respond to many activating stimuli. The elevation of intracellular cAMP has been associated with immunosuppressive and anti-inflammatory activities and represents a potential treatment of asthma.Our aim was to evaluate the impact of the deletion of the murine phosphodiesterase (PDE)7B gene and then to evaluate the efficacy of a newly de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…No inhibition in T lymphocyte proliferation or cytokine production by Th1 and Th2 cells after CD3/CD28 co-stimulation was observed. A similar conclusion resulted from a study conducted by Chevalier et al [51], who reported that PDE7 was not involved in an experimental model of asthma in ovalbumin-immunized mice. A deletion of the PDE7B gene in knockout mice had no effect on the following tested parameters: airway hyperreactivity, cytokine levels in bronchoalveolar lavage, inflammatory cell infiltration, and total IgE in serum.…”
Section: Phosphodiesterase 7 (Pde7) Family In T Cellssupporting
confidence: 76%
See 1 more Smart Citation
“…No inhibition in T lymphocyte proliferation or cytokine production by Th1 and Th2 cells after CD3/CD28 co-stimulation was observed. A similar conclusion resulted from a study conducted by Chevalier et al [51], who reported that PDE7 was not involved in an experimental model of asthma in ovalbumin-immunized mice. A deletion of the PDE7B gene in knockout mice had no effect on the following tested parameters: airway hyperreactivity, cytokine levels in bronchoalveolar lavage, inflammatory cell infiltration, and total IgE in serum.…”
Section: Phosphodiesterase 7 (Pde7) Family In T Cellssupporting
confidence: 76%
“…Regarding respiratory diseases, PDE7 inhibitors may have beneficial effects in asthma and COPD due to relaxation of airway smooth muscles and anti-inflammatory properties [67,68], as well as in smoke-induced lung inflammation in mice [69]. However, Chevalier et al [51] showed no effects of PDE7 inhibition in an experimental model of asthma in mice. Some studies demonstrated that PDE7 inhibitors, PDE4/7 inhibitor or a combination of PDE3, 4, and 7 inhibitors induced apoptosis of leukemic cells [45,46,70].…”
Section: Potential Therapeutic Use Of Selective Pde7 Inhibitorsmentioning
confidence: 99%
“…Since PDE7 involved in T cell activation, PDE7 had been considered as a potential therapeutic target for chronic inflammatory diseases including asthma and COPD [46,47,48]. However, a study showed no involvement of PDE7A and PDE7B in the asthmatic mice model of ovalbumin-induced airway inflammation and hyper-reactivity [49]. To the best of our knowledge, no literature has reported the suppressive effect of miR-10a-5p or miR-146a-5p on PDE7A .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that activation of the cAMP/PKA signaling pathway in mast cells can mitigate its degranulation and inhibit allergic reaction [45]. Elevated cAMP levels can exert immunosuppressive and antiinflammatory effects in cells, which is a potential treatment for autoimmune diseases [46]. Phosphodiesterase 4 (PDE4) refers to an enzyme degrading cAMP.…”
Section: Discussionmentioning
confidence: 99%